2016
DOI: 10.1161/hypertensionaha.115.06674
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Maternal Cardiac Dysfunction After Preeclampsia Identifies Patients at Risk for Recurrent Preeclampsia

Abstract: Maternal cardiovascular health represents the key point for developing an uneventful pregnancy, and its proper function is important for a normal evolution of pregnancy. Serious pregnancy-related hypertensive disorders such as preeclampsia might entail severe future effects on women's health even after delivery and influence the long-term quality of life as well as the following pregnancy outcomes. A proper maternal cardiovascular adaptation to the pregnancy plays a key role for preventing gestational hyperten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 41 publications
1
50
0
1
Order By: Relevance
“…44 In addition, these changes allow for early identification of women at highest risk of recurrent preeclampsia in their next pregnancy and, therefore may also provide an opportunity for intervention to mitigate future cardiovascular disease. 45 Once detected, subclinical changes in cardiac function may be amenable to cardioprotective therapies, such as β-blocker use. Previous work has demonstrated that in patients receiving cardiotoxic chemotherapy, β-blocker administration reversed worsening of longitudinal strain.…”
Section: Discussionmentioning
confidence: 99%
“…44 In addition, these changes allow for early identification of women at highest risk of recurrent preeclampsia in their next pregnancy and, therefore may also provide an opportunity for intervention to mitigate future cardiovascular disease. 45 Once detected, subclinical changes in cardiac function may be amenable to cardioprotective therapies, such as β-blocker use. Previous work has demonstrated that in patients receiving cardiotoxic chemotherapy, β-blocker administration reversed worsening of longitudinal strain.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the list of predisposing factors for PE is almost the same as that for CKD, once more stressing the similarities between these diseases ( Table 2). Further elements, including genetic predisposition, are included in the list of risk factors for recurrent PE; once again, the similarities with CKD are evident [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79]. However, in most of these lists there is an important overlap between predisposing maternal diseases, including CKD, and specific conditions that may impair placentation, including parity or genetic factors.…”
Section: Introductionmentioning
confidence: 99%
“…This result aligns with findings of persistent cardiac hypertrophy up to a year postpartum in a subset of preeclamptic women. 7, 53 …”
Section: Discussionmentioning
confidence: 99%